Tyrosinase and catecholase-like activities of a dinuclear Cu(II) complex. (15th February 2018) - Chatterjee, Arnab; Yadav, Hare Ram; Choudhury, Angshuman Roy; Ali, Anzar; Singh, Yogesh; Ghosh, Rajarshi
Graphical abstract: A dinuclear antiferromagnetically coupled Cu(II) complex was synthesized and characterized crystallographically. The compound was found to had tyrosinase-like activity resulting in conversion of 2, 4-di-tert-butylphenol to 3, 5-di-tert-butylcatechol to 3, 5-di-tert-butylquinone. 3, 5-Di-tert-butylcatechol and 3, 5-di-tert-butylquinone were characterized using analytical and spectroscopic methods. The compound was also found to give catecholase-like activity in methanol and acetonitrile. Abstract: A dinuclear Cu(II) complex was synthesized and crystallographically characterized. The compound was found to have antiferromagnetic interaction in between the Cu(II) centres in the molecule. It had weak intermolecular ferromagnetic interaction. The compound was found to be tyrosinase and catecholase active. In case of tyrosinase activity, the diphenol formed was isolated using thin layer chromatography (TLC) and characterized through 1 H NMR as well as mass spectrometry. The o -quinone derivative formed in this reaction was characterized using GC–MS. The latter activity was monitored spectrophotometrically and the product o -quinone derivative was isolated (in MeOH and MeCN) column chromatographically and characterized using melting point determination. These were followed by Michealis–Menten kinetics with turnover numbers 4.95 × 10 3 and 1.58 × 10 3 h −1 in MeOH and MeCN, respectively.